2021
DOI: 10.3389/fcell.2021.723108
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy in Antiviral Immunity

Abstract: Mitochondria are important organelles whose primary function is energy production; in addition, they serve as signaling platforms for apoptosis and antiviral immunity. The central role of mitochondria in oxidative phosphorylation and apoptosis requires their quality to be tightly regulated. Mitophagy is the main cellular process responsible for mitochondrial quality control. It selectively sends damaged or excess mitochondria to the lysosomes for degradation and plays a critical role in maintaining cellular ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…More recently, other innate immune molecules, such as cGAS, NLRX1, TRAF6, NLRP3, and IRGM, have been functionally associated with mitochondria (Arnoult et al, 2011; Qiu et al, 2023). The accumulating evidences suggest that viruses eliminate critical immune molecules within mitochondria by reducing mitochondrial mass to evade immune response (Mehrzadi et al, 2021; Wang et al, 2021a). For instance, the influenza A virus PB1-F2 protein degrades MAVS by triggering mitophagy (Wang et al, 2021b); coronaviruses, including SARS-CoV-2, promote their replication by altering mitochondrial dynamics and targeting MAVS (Mehrzadi et al, 2021; Shang et al, 2021); ZIKV NS4A induces mitochondrial fission and mitophagy to suppress MAVS-mediated IFN-I response (Lee and Shin, 2023); DENV disrupts mitochondrial biogenesis by downregulating the master regulators PPARγ and PGC1α (Singh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, other innate immune molecules, such as cGAS, NLRX1, TRAF6, NLRP3, and IRGM, have been functionally associated with mitochondria (Arnoult et al, 2011; Qiu et al, 2023). The accumulating evidences suggest that viruses eliminate critical immune molecules within mitochondria by reducing mitochondrial mass to evade immune response (Mehrzadi et al, 2021; Wang et al, 2021a). For instance, the influenza A virus PB1-F2 protein degrades MAVS by triggering mitophagy (Wang et al, 2021b); coronaviruses, including SARS-CoV-2, promote their replication by altering mitochondrial dynamics and targeting MAVS (Mehrzadi et al, 2021; Shang et al, 2021); ZIKV NS4A induces mitochondrial fission and mitophagy to suppress MAVS-mediated IFN-I response (Lee and Shin, 2023); DENV disrupts mitochondrial biogenesis by downregulating the master regulators PPARγ and PGC1α (Singh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Two primary pathways for dealing with damaged mitochondria are proposed, including mitochondrial quality control mechanisms to immediately process defective or misfolded/mislocalized mitochondrial proteins and mitophagy that delivers irreversibly damaged mitochondria to the lysosome for degradation ( 31 , 69 ). Mitophagy is mainly controlled by the ubiquitin (Ub)-dependent [PTEN-induced kinase 1 (PINK1)/Parkin RBR E3 ubiquitin-protein ligase (Parkin)] ( 70 ) or Ub-independent (specific LIR-containing receptor-dependent) pathways, such as those mediated by BNIP3 (BCL2 interacting protein 3), BNIP3L (BNIP3-like, also called NIX), FUNDC1 (FUN14 domain containing 1), PHB2 (prohibitin 2), BCL2L13 (BCL2-like protein 13), and FKBP8 (FK506-binding protein prolyl isomerase 8) ( 67 , 71 ).…”
Section: Regulation Of Innate Immune Responses By Mitophagymentioning
confidence: 99%
“…Deficient mitophagy caused by autophagy related 5 (ATG5) ablation increases mtROS production and elevates levels of MAVS, promoting the activation of the type I IFN pathway ( 72 ). Sequestosome 1 (SQSTM1/p62)-dependent mitophagy ( 73 ) and mitophagy induced by viral proteins ( 71 , 74 ) also regulate the type I IFN response. By contrast, NIX-dependent mitophagy acts as an intrinsic negative regulator of the RLRs-MAVS axis by preventing spontaneous aggregation of endogenous MAVS in the absence of viral infection ( 75 ).…”
Section: Regulation Of Innate Immune Responses By Mitophagymentioning
confidence: 99%
“…Notably, there are various pathways involved in autophagy. Mitophagy is a selective autophagy that can specifically remove damaged or excess mitochondria and maintain cellular homeostasis (Wang H. et al, 2021b). In 2016, Kim et al found that SESN2 could suppress sepsis by inducing mitophagy and inhibiting NLRP3 activation in macrophages.…”
Section: Interaction Of Pyroptosis and Autophagy In Sepsismentioning
confidence: 99%